2020
DOI: 10.1177/0284185120950108
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound for the preoperative assessment of laryngeal carcinoma: a preliminary study

Abstract: Background Contrast-enhanced ultrasound (CEUS) is considered an attractive imaging technique to evaluate tumor microcirculation. However, the validity of CEUS for assessing laryngeal carcinoma is unclear. Purpose To compare the performance of CEUS with conventional US and contrast-enhanced computed tomography (CECT) in the diagnosis and preoperative T-staging of laryngeal carcinoma. Material and Methods Forty-one consecutive patients with laryngeal carcinoma underwent conventional high-frequency US, CEUS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Duplex sonography of the great cervical vessels can be performed during the same investigation to exclude stenosis of the carotid artery [ 33 ]. In addition Hu et al [ 37 ] proposed contrast-enhanced ultrasound (CEUS) as a complementary modality for the detection and pretherapeutic staging of laryngeal carcinoma, revealing perfusion characteristics of tumors. According to the author, CEUS has a reliable T-staging accuracy and diagnostic power for detecting laryngeal cartilage invasion (Sensitivity, specificity, and accuracy in the evaluation of involvement of thyroid cartilage by CEUS of 92.9%, 87.5%, and 90.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplex sonography of the great cervical vessels can be performed during the same investigation to exclude stenosis of the carotid artery [ 33 ]. In addition Hu et al [ 37 ] proposed contrast-enhanced ultrasound (CEUS) as a complementary modality for the detection and pretherapeutic staging of laryngeal carcinoma, revealing perfusion characteristics of tumors. According to the author, CEUS has a reliable T-staging accuracy and diagnostic power for detecting laryngeal cartilage invasion (Sensitivity, specificity, and accuracy in the evaluation of involvement of thyroid cartilage by CEUS of 92.9%, 87.5%, and 90.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Specificity: 95.6% 11 Gritzmann [ 33 ] 1989 Austria Assessment of laryngeal cancer and other laryngeal lesions Assessment of advanced laryngeal cancer 37 Sensitivity: 95%. Specificity: 73% 12 Hu [ 37 ] 2021 China Assessment of laryngeal cancer and other laryngeal lesions Preoperative assessment of laryngeal carcinoma 38 Accuracy rate: 82.9% for conventional US, 87.8% for CEUS, and 90.2% 13 Huang [ 31 ] 2019 China Diagnosis of laryngeal disorders in infants and children Diagnosis of infant laryngomalacia 40 Sensitivity: 96.3%. Specificity: 84.6% 14 Kandil [ 23 ] 2016 USA Evaluation of vocal cords function Evaluation of preoperative and postoperative vocal fold function in patients undergoing thyroid or parathyroid surgery 250 Sensitivity of 53.8%; Specificity of 50.5% 15 Klinge [ 28 ] 2016 Germany Diagnosis of laryngeal disorders in infants and children Visualization of laryngeal structures and vocal fold movements of children using synchronous video laryngoscopy and laryngeal sonography 35 Sonography-only identification rate: 80%.…”
Section: Methodsmentioning
confidence: 99%
“…In the study by Xia et al [21], the authors concluded that ultrasound may be more accurate than CT in evaluating invasion of the paraglottic space and thyroid cartilage, thus making it an effective complement to CT imaging. A recent preliminary study showed that contrast-enhanced ultrasound appears promising and may become another reliable tool for staging of laryngeal cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…CEUS examination was performed by administering an intravenous bolus of SonoVue (Bracco SpA, Milan, Italy) (5 mL, followed by saline flush) [14]. The scan was performed with a frequency of 12 MHz and a mechanical index of 0.8.…”
Section: Ceus Examinationmentioning
confidence: 99%
“…Moreover, it has been widely used in clinical practice to diagnose hepatic and renal pathologies [12,13]. In a recent publication, CEUS showed potential in assessing non-ossified thyroid cartilage invasion [14]. Non-ossified thyroid cartilage and adjacent laryngeal cancer are well visualized on CEUS due to the differences between non-enhancing non-ossified thyroid cartilage and enhancing adjacent laryngeal cancer.…”
Section: Introductionmentioning
confidence: 99%